Certificación de productores ecológicos en SGP Lima: Reporte basado en la estrategia de la intervención piloto - Muñoz, M.; Ventocilla, D.; Fonseca, C.; Pradel, W. (International Potato Center, 2023)
In 2022, Peru led the food insecurity table in South America, registering 16.6 million Peruvians in this situation, the most vulnerable families had to reduce their food intake to once a day. The Institute of Development and Environment – IDMA, in alliance with the International Potato Center – CIP, within the framework of the CGIAR research on "Resilient cities through sustainable urban and peri-urban agri-food systems", has been organizing the development of an awareness campaign for World Food Day, concerning the contribution provided by agroecological family farming located in the Valleys of Metropolitan Lima. The central part of this strategy was the forum: ”DIALOGUES ABOUT HEALTHY DIETS FOR EVERYONE, 3X7”; this space was creates with the purpose of dialogue and reflection in relation to healthy diets, where the roles that small farmers have been fulfilling for the generation of food were identified and highlighted. Likewise, the importance of common soup kitchens was highlighted to provide food in low-resource areas and how vegetable producers have been articulated, mainly at the level of urban agriculture to provide inputs for common soup kitchens.